Effects of Economic Freedom on Subjective Well-Being - Alexandra-Cristina Sirbu; Andreea-Oana Iacobuță-Mihăiță; Mircea Asandului; Madalina-Maria Brezuleanu (Scientific Annals of Economics and Business, 2023)
Are people more likely to be satisfied with their lives if they had freedom from regulations, if they had the ability to trade freely internationally? In light of the demographic aging phenomenon we are facing, the present study analyzes the relationship between economic freedom and life satisfaction among European older adults. In order to do so, we are using data from the European Health, Ageing, and Retirement Survey and Economic Freedom of the World. By using the ordered logit regression method, we estimated different models to identify how sub-indicators of economic freedom affect the subjective well-being. According to the findings, the quality of the institutions that define the legal system and establish rules for the protection of private property and sound monetary policy have a positive effect on subjective well-being. On the other hand, openness to international trade has a negative effect and government and regulation doesn’t show any significance.